Sarcocystis entzerothi n. sp. from the European roe deer (Capreolus capreolus) - Prakas, Petras; Rudaitytė-Lukošienė, Eglė; Butkauskas, Dalius; Kutkienė, Liuda (Parasitology Research, 2017)
In the present study, we describe Sarcocystis entzerothi n. sp. from the European roe deer (Capreolus capreolus) based on the microscopical and DNA analysis. By light microscopy (LM), cysts of S. entzerothi were spindle-shaped with pointed tips, 950–1900 × 70–150 μm in size and had 5–6 μm long finger-like cyst wall protrusions. Cyst wall of S. entzerothi by transmission electron microscopy (TEM) was type 10a-like; villar protrusions were up to 1.2 μm wide, densely packed, lying about 0.1 μm between each other, had profuse microgranules and microfilaments, parasitophorous vacuolar membrane had many minute invaginations, and the ground substance layer measured up to 0.4 μm. This species is morphologically similar to Sarcocystis silva, previously found in the roe deer and the moose (Alces alces). By LM, cysts of S. silva were cigar-shaped with blunted tips, measured 1000–1500 × 130–184 μm, and had 7–8 μm long finger-like cyst wall protrusions. Under TEM, S. silva had no clear differences from S. entzerothi in their cyst wall ultrastructure. Having examined six roe deer hunted in Lithuania, cysts of S. entzerothi and S. silva were identified in four and two animals, respectively. These two Sarcocystis species could be morphologically differentiated according to the shape of the cysts and the length of protrusions. The species examined showed 95.6–96.1 % and 85.6–86.9 % sequence identity within 18S ribosomal DNA (rDNA) and cox1, respectively, and therefore they could be clearly distinguished by means of molecular methods. It should be noted that in the 18S rDNA phylogenetic tree, S. entzerothi from the roe deer was placed together with one sequence of Sarcocystis sp. from the Lithuanian red deer (Cervus elaphus) demonstrating the same species. Based on 18S rDNA and cox1 sequences, S. entzerothi was more closely related to Sarcocystis species transmitted via felids than canids.